Knee kinematics and kinetics during shuttle run cutting: Comparison of the assessments performed with and without the point cluster technique - Ishii, H.; Nagano, Y.; Ida, H.; Fukubayashi, T.; Maruyama, T. (Journal of Biomechanics, 2011)
The differences between the assessments performed with and without the point cluster technique (PCT) for knee joint motions during the high-risk movements associated with non-contact anterior cruciate ligament (ACL) injuries have not been reported. This study aims to examine the differences between PCT and non-PCT assessments for knee joint angles and moments during shuttle run cutting. Fourteen high school athletes performed a maximal effort shuttle run cutting task. Motion data were collected by an 8-camera motion analysis system at 200 Hz, and ground reaction force data were recorded using a force plate at 1000 Hz. In both PCT and non-PCT approaches, the knee joint angles were calculated using Euler angle rotations, and the knee joint moments were obtained by solving the Newton-Euler equations using an inverse dynamics technique. For the extension/flexion angle, good agreement was measured between PCT and non-PCT assessments. The abduction angle obtained in the non-PCT assessment was smaller than that obtained with the PCT. An internal rotation angle was obtained in the PCT assessment, whereas a small external rotation angle was obtained in the non-PCT assessment. For the knee joint moments, good agreement between PCT and non-PCT assessments was observed for all the components. The differences in the knee joint angles were attributed in part to the differences in the position of the medial femoral epicondyle. The results suggest that the ACL injury risk during shuttle run cutting is estimated lower in the non-PCT assessment than in the PCT assessment.